Climate Change Impact on Temperature, Rainfall, and Humidity in Batang Toru, South Tapanuli - Siregar, Anjeli Agustina; Berliani, Riska; Abrar, Camelia Batun; Suhendra, Suhendra; Lizalidiawati, Lizalidiawati (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Batang Toru is a sub-district in South Tapanuli Regency that is vulnerable to climate change due to forest conversion to gold mining. This is thought to be the cause of climate change in Batang Toru. This study aims to determine climate variability due to the influence of gold mining in Batang Toru. This research can provide useful information for designing policies, reducing risks, and improving operational sustainability at the Batang Toru mine. The data used are monthly mean temperature, rainfall, and humidity data for 5 years before and after mining operations (1992-1996 and 2018-2022) obtained from BMKG FL Tobing Meteorological Station and NASA. The methods used are descriptive, quantitative, and correlation analysis of temperature, rainfall, and humidity data. Data processing uses Panoply software to create 2D distribution maps and Microsoft Excel to see the time series of each data. The results showed that temperature variability increased by 0.53°C. Batang Toru's rainfall variability is of the equatorial type, with peaks occurring in October and April. The average humidity value for the last 5 years was 84.88% and previously it was 82.88%. Based on the results of the study, it is known that the impact of gold mining operations has greatly affected climate variability in Batang Toru.